NANOSTRUCTURE LIPID CARRIER TECHNOLOGY IN DRUG DELIVERY: ROUTE OF ADMINISTRATION, PREPARATION METHOD, CHARACTERIZATION, AND APPLICATION FOR ANTI-AGING - Muliana, Muliana; Alatas, Fikri (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
The new method, known as nanostructured lipid carrier (NLC) in drug delivery systems, has the potential to increase therapeutic efficacy, stability, and bioavailability. This systematic literature review aimed to provide a detailed summary of NLC technology in drug delivery systems, including routes of administration, preparation methods, characterization, and utilization for the delivery of anti-aging active ingredients in cosmetics. To collect scholarly articles on NLCs, we employed a systematic search method using Google Scholar and PubMed. After the screening process, 53 pertinent papers out of 102 articles were chosen for descriptive analysis. NLC exhibit significant promise in many drug delivery applications, including oral, topical, parenteral, and transmucosal routes, with many benefits, including improved bioavailability, stability, and drug penetration through the skin, cornea, and brain. Moreover, NLC technology has been effectively applied for the administration of drugs, including anti-aging drugs. Topical anti-aging preparations generally use synthetic or natural active ingredients. However, synthetic ingredients are often less stable and can irritate skin. NLC can protect and control the release of active ingredients, thereby reducing the risk of irritation. NLC can also improve the penetration of active ingredients into the deeper layers of the skin, allowing it to reach the dermis layer, which is responsible for most skin aging. The efficient absorption capacity of NLC technology in topical preparations presents new opportunities for anti-aging cosmetic product development owing to its effectiveness in skin penetration. Keywords: Nanostructured Lipid Carrier (NLC), drug delivery system, drug penetration, anti-aging